Emergencja – podręcznik dla mało opornych - Komorowska-Mach, Joanna (Filozofia Nauki, 2010)
The review tries to summarize the main topics covered by the book "Między redukcją a emergencją" by Robert Poczobut and also to highlight certain points that might be controversial to the philosophically-oriented reader. In particular, Poczobut's methodological claims regarding the boundary between natural sciences and philosophy of mind are brought under scrutiny. While the book presents a broad range of views on matters regarding emergence and reduction, especially with respect to the psychophysical problem, it remains to be proven that the views presented by the author are in reality the most viable option that a philosopher of mind wishing to conform to scientific results has at her disposal.